A Comparative Analysis of Qur'anic Educational Methodologies in Pepeling Jeung Panggeuing and Mencandai Tuhan - Nurlatipah Nurlatipah; Dedi Suryadi; Lilis Lisnawati; Cecep Nasrul Yakin (Journal of Mandalika Social Science, 2026)
This study aims to analyze five Qur’anic educational methodologies—al-qishah (narrative storytelling), al-amtsal (parables), al-hiwar (argumentative dialogue), targhīb wa tarhīb (motivation and warning), and mau'iẓah (heartfelt counsel)—as implemented in Pepeling Jeung Panggeuing by KH. Aceng Zakaria (Ibn Azka Press, 2021), and to compare them with the approach adopted by Jajang A. Rohmana in Mencandai Tuhan: Anekdot Hoofd Penghulu Bandung Haji Hasan Mustapa 1852–1930 (Gunung Djati Publishing, 2024). Employing a qualitative approach based on textual analysis and comparative study, this research finds that KH. Aceng integrates all five Qur’anic methodologies within a normative-contextual framework characteristic of the Persis pesantren tradition, with mau'iẓah hasanah serving as the core of his da‘wah, supported by anecdotal al-qishah, Sundanese-rooted al-amtsal, manthiq-based al-hiwar, and targhīb wa tarhīb functioning as an affective motivational force. In contrast, through his historical reconstruction of Haji Hasan Mustapa’s anecdotes, Jajang A. Rohmana adopts an academic-descriptive epistemological approach that positions these methodologies as objects of inquiry rather than instruments of da‘wah. The common ground between the two works lies in their use of Sundanese-language anecdotes as a serious epistemological medium for the transmission of Islamic values, while their differences stem from fundamentally distinct objectives, normative foundations, and methodological frameworks.